ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PADA SISTEM KREDIT DENGAN AGUNAN DI PT. BANK PERKREDITAN RAKYAT (BPR) MAROBA ITE CABANG BENGKULU - subaeti subaeti subaeti (Jurnal Ilmu Akuntansi, 2018)
Abstract This study aims to determine the applications of the accounting system on credit system with collateral in PT. BPR Maroba Ite branch of Bengkulu city and compare the existing theory with practice in the field. The nature of this research is descriptive, the type of data used are qualitative data, sources of data used are primary, that is the result of interviews and secondary data is information the compny’s history, credit system with collateral in PT. BPR Maroba Ite Branch of Bengkulu City. The population used in this research is accounting information system on credit system with collateral data in PT. BPR Maroba Ite Branch of Bengkulu city from 2013-2016. The wording in writing using a flow chart. Based on the boarding application of accounting information system on credit system with collateral data in PT. BPR Maroba Ite Branch of Bengkulu city that the company has implemented an accounting information system on the credit system with good collateral regarding the recording of accountability of transactions, dcuments or forms used in order to minimize the risk of bad debts evident from the table of the number of Net Perfoarming Loan showing the number of non perfoarming loans from october 2013 to december 2016 is not more than 5% but only 3,60% according to the standard percentage of non perfoarming loans in the fair cetegory of Indonesian Bank Number 15/2/PBI/2013, Number 17/11/PBI/2015 and Financial Services Authority (OJK) Regulation Number 20/POJK.03/2014, as well as the handling or solution of bad debts that are applied are good with restructuring and negotiation in accordance with banking regulations stipulated in Bank Indonesia Regulation Number 7/2/PBI/2005 and the regulation of the Financial Services Authority Number 11/POJK.03.2015.